Experimental and Computational Studies towards Chemoselective C−F over C−Cl Functionalisation: Reversible Oxidative Addition is the Key. Issue 2 (17th November 2020) - Jacobs, Emily; Keaveney, Sinead T.
Abstract: Catalytic cross‐coupling is a valuable tool for forming new carbon‐carbon and carbon‐heteroatom bonds, allowing access to a variety of structurally diverse compounds. However, for this methodology to reach its full potential, precise control over all competing cross‐coupling sites in poly‐functionalised building blocks is required. Carbon‐fluorine bonds are one of the most stable bonds in organic chemistry, with oxidative addition at C−F being much more difficult than at other C‐halide bonds. As such, the development of methods to chemoselectively functionalise the C−F position in poly‐halogenated arenes would be very challenging if selectivity was to be induced at the oxidative addition step. However, metal‐halide complexes exhibit different trends in reactivity to the parent haloarenes, with metal‐fluoride complexes known to be very reactive towards transmetalation. In this current work we sought to exploit the divergent reactivity of Ni−Cl and Ni−F intermediates to develop a chemoselective C−F functionalisation protocol, where selectivity is controlled by the transmetalation step. Our experimental studies highlight that such an approach is feasible, with a number of nickel catalysts shown to facilitate Hiyama cross‐coupling of 1‐fluoronapthalene under base free conditions, while no cross‐coupling with 1‐chloronapthalene occurred. Computational and experimental studies revealed the importance of reversible C−Cl oxidative addition for the development of selective C−F functionalisation, with ligand effects on the potential for reversibility also presented. Abstract : Nickel catalysis : Base‐free Hiyama cross‐coupling of unactivated fluoroarenes was developed, demonstrating that efficient, mono‐metallic C−F activation can be achieved using nickel catalysis. Experimental and computational investigations into the potential for selective C−F cross‐coupling in the presence of more active C‐halides were performed, highlighting that transmetalation‐controlled C−F selectivity may be possible if reversible oxidative addition can be achieved.